VALUASI EKONOMI DENGAN METODE TRAVEL COST PADA WISATA TAMAN KEANEKARAGAMAN HAYATI KABUPATEN MESUJI - Susan Novita; Zainal Abidin; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This research aims to analyze visitor satisfaction on tourism facilities and infrastructures, travel cost, factors that affect the number of visits, and economic value of Taman Kehati in Mesuji Regency.  This research used a survey method involving 65 respondents.  Data were collected in December 2019.  The first objective was analized using likert scale analysis, the second objective used travel cost method, the third objective used multiple linear regression analysis, and the fourth objective used consumer surplus analysis.  The study suggests that visitors were satisfied with facilities and infrastructure provided by Taman Kehati, travel cost was IDR165.614 per individual with the highest cost allocated for consumption, which was IDR101.656,72 or 61 percent of total travel cost.  The factors affecting the number of visits to Taman Kehati included age, income, travel cost, travel time, day of the visit, and conditions of the park.  The economic value of Taman Kehati is IDR993.850.777.736 per year. Key words: economic value, travel costs, visitor satisfaction.